2016
DOI: 10.1016/j.celrep.2015.12.094
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Reprogramming of Pancreatic Cancer Mediated by CDK4/6 Inhibition Elicits Unique Vulnerabilities

Abstract: Due to loss of p16ink4a in pancreatic ductal adenocarcinoma (PDA), pharmacological suppression of CDK4/6 could represent a potent target for treatment. In PDA models CDK4/6 inhibition had variable effect on cell cycle, but yielded accumulation of ATP and mitochondria. Pharmacological CDK4/6 inhibitors induce cyclin D1 protein levels; however, RB activation was required and sufficient for mitochondrial accumulation. CDK4/6 inhibition stimulated glycolytic and oxidative metabolism and was associated with an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
144
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 52 publications
25
144
1
Order By: Relevance
“…Interestingly, we have shown that in addition to cell cycle inhibition, palbociclib also suppresses the activity of mTOR’s downstream mediators, p70S6K and S6, likely potentiating the metabolic effects. In line with previous studies (38), we demonstrated that palbociclib activates mTOR—which is likely due to feedback mechanisms from suppression of mTOR downstream mediators, of cellular metabolism, and of the cell cycle. Contrasting with our results, a recent report on palbociclib-induced metabolic reprogramming in Ras-mutated pancreatic cancer (38) showed that palbociclib treatment activated both glycolytic and mitochondrial metabolism through mTOR activation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, we have shown that in addition to cell cycle inhibition, palbociclib also suppresses the activity of mTOR’s downstream mediators, p70S6K and S6, likely potentiating the metabolic effects. In line with previous studies (38), we demonstrated that palbociclib activates mTOR—which is likely due to feedback mechanisms from suppression of mTOR downstream mediators, of cellular metabolism, and of the cell cycle. Contrasting with our results, a recent report on palbociclib-induced metabolic reprogramming in Ras-mutated pancreatic cancer (38) showed that palbociclib treatment activated both glycolytic and mitochondrial metabolism through mTOR activation.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies (38), we demonstrated that palbociclib activates mTOR—which is likely due to feedback mechanisms from suppression of mTOR downstream mediators, of cellular metabolism, and of the cell cycle. Contrasting with our results, a recent report on palbociclib-induced metabolic reprogramming in Ras-mutated pancreatic cancer (38) showed that palbociclib treatment activated both glycolytic and mitochondrial metabolism through mTOR activation. These differences could be due to the presence of Ras mutation in the pancreatic cancer model or to the different tissue contexts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…45 Tumor cell arrest during the G1/S transition, by inhibitors of Cdk4/6, is one of the new avenues for breast carcinoma treatment. 46 While such treatment successfully reduces tumor size, it may also accumulate reactive oxygen species and increase Cyclin D1 expression, 47 which have been linked to increased migration and invasion. 48,49 Hence, understanding of the coordination between cell cycle and cell migration, as well as the other hallmarks of metastasis is increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Use of these inhibitors will need to account for potential compensatory responses leading to drug resistance or tumor growth exacerbation. For instance, pharmacologic inhibition of CDK4/6 leads to accumulation of mitochondria and reactive oxygen species (ROS) and activation of mTORC1 signaling in PDA cells, while enhanced cell cycle arrest or cytotoxicity can be achieved with the further addition of inhibitors for MTORC, MEK, BCL2 and/or ROS scavenging [51]. …”
Section: The Molecular Landscape Of Pancreatic Cancer: New Therapeutimentioning
confidence: 99%